2019
DOI: 10.3390/w11010147
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of SWAT and Two Data-Driven Models for a Data-Scarce Mountainous Headwater in Semi-Arid Konya Closed Basin

Abstract: Hydrologic models are important tools for the successful management of water resources. In this study, a semi-distributed soil and water assessment tool (SWAT) model is used to simulate streamflow at the headwater of Çarşamba River, located at the Konya Closed Basin, Turkey. For that, first a sequential uncertainty fitting-2 (SUFI-2) algorithm is employed to calibrate the SWAT model. The SWAT model results are also compared with the results of the radial-based neural network (RBNN) and support vector machines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 49 publications
4
17
0
Order By: Relevance
“…Figure 4 shows two isohyet maps of the event corresponding to the coverage generated from the accumulated precipitation in two of these intervals (the event requires the use of 981 layers). Spatial interpolation is performed by applying a distributed precipitation model based on the use of radial basis functions (RBF) [66][67][68]. From this precipitation coverage, the computer program can generate a different hyetograph for each point of the basin.…”
Section: Rainfall Modelmentioning
confidence: 99%
“…Figure 4 shows two isohyet maps of the event corresponding to the coverage generated from the accumulated precipitation in two of these intervals (the event requires the use of 981 layers). Spatial interpolation is performed by applying a distributed precipitation model based on the use of radial basis functions (RBF) [66][67][68]. From this precipitation coverage, the computer program can generate a different hyetograph for each point of the basin.…”
Section: Rainfall Modelmentioning
confidence: 99%
“…Data‐driven methods, for example SVM, show good performance in simulation and prediction of soil moisture (Bordoni et al, 2017; Ezzahar et al, 2019). Compared with the hydrological models, SVM needs much fewer input variables (Khwairakpam et al, 2018; Koycegiz & Buyukyildiz, 2019). Therefore, the investigation on its application is meaningful for the data limited regions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the investigation on its application is meaningful for the data limited regions. Some studies prove that it is possible for SVM to achieve similar or even better simulation results than physical models, although they are for streamflow simulation/prediction rather than for soil moisture simulation/prediction (Jajarmizadeh, Kakaei Lafdani, Harun, & Ahmadi, 2014; Koycegiz & Buyukyildiz, 2019; Zhang, Srinivasan, & Van Liew, 2009). For instance, Koycegiz and Buyukyildiz (2019) found that SVM shows better performance in simulating streamflow at the headwater of Çarsamba River, compared with water assessment tool (SWAT) model.…”
Section: Introductionmentioning
confidence: 99%
“…Noori & Kalin (2016) employed the SWAT and ANN models in order to perform stream flow estimations at 29 watersheds located around Atlanta during hot and cold seasons. At the end of the study, higher accuracy was attained in hot seasons than in cold seasons (Koycegiz & Buyukyildiz 2019). Afkhamifar & Sarraf (2020) investigated a hybrid wavelet-transform-based extreme learning machine (ELM) model predicting GWL.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have compared both models for daily stream flow estimation. (Koycegiz & Buyukyildiz 2019) investigated the performance of two SWAT and Data-Driven Models (the RBNN and the SVR models) for simulating river runoff in Turkey. The results showed that the data-driven models were more successful than the SWAT model, although the SWAT model is a comprehensive physical model and has a significant problem-solving capability (Eini et al 2020b).…”
Section: Introductionmentioning
confidence: 99%